The multiple mediation roles of trust and satisfaction in the effect of perceived corporate social responsibility on loyalty - Uslu, Abdullah; Şengün, Halil İbrahim (Business, Management and Economics Engineering, 2021)
Purpose – This study aims at investigating the effect of corporate social responsibility perceptions of local people living in Diyarbakır on bank loyalty in terms of banking services and the mediator roles of trust and satisfaction in this effect.Research methodology – Cronbach’s Alpha coefficients, reliability, convergent and discriminant validity and multicollinearity were examined before testing the hypotheses of the research. The validity of the measurement model for the variables that are included in the model was examined by the confirmatory factor analysis. Partial least squares path modelling was used to analyze the research model and hypotheses, and multiple mediation analysis was used to test the mediation effects. The collected data were analyzed by the software SPSS 22.0 and SmartPLS 3.3.0.Findings – The research results exposed that the corporate social responsibility perceptions of bank customers have significant and positive effects on bank loyalty. Furthermore, satisfaction has had partial mediation effects on the relationship between CSR perception and loyalty.Research limitations – The population covers individuals with regular wage or salary who live in Diyarbakır. The survey was conducted between October 1 and December 1, 2019, with convenience sampling technique and 400 questionnaires were collected.Practical implications – When conducting CSR activities, businesses should emphasize that trust and satisfaction have an essential effect as well as loyalty.Originality/Value – This study investigated the simultaneous multiple mediator effects of trust and satisfaction in the relationship between CSR and loyalty.